Is greater flexibility in the labour market the answer to the unemployment crisis? - Ulrich Walwei (Intereconomics, 1996)
In view of high and persistent unemployment in the European industrialised countries there is growing consensus that more flexibility is needed with regard to both the legal and institutional conditions governing the labour market (external flexibility) and the management of human resources within individual firms (internal flexibility). This article examines the interaction between internal and external flexibility with special reference to wages, working time and job security.
Keywords: 330; Unemployment